Hubungan Kemampuan Berpikir Kreatif Dengan Keterampilan Menulis Karangan Narasi Siswa Kelas V SDN 12 Singkawang - Octavianti, Nabilla; Sunarsih, Eti; Sulistri, Emi (Universitas Indraprasta PGRI, 2024)
This research aims to: 1) determine the creative thinking abilities of class V studentsat SDN 12 Singkawang; 2) to determine the creative thinking abilities of class Vstudents at SDN 12 Singkawang; 3) to determine the correlation between creativethinking skills and narrative essay writing skills for fifth grade students at SDN 12Singkawang. The method utilized in this research is quantitative research with acorrelation design. The research population was 47 class V students at SDN 12Singkawang. The sampling technique in this research was saturated sampling of 47students. The data collection technique in this research is based on measurementtechniques, namely using tests of creative thinking abilities and narrative essaywriting skills. The data analysis techniques used are Product Moment Correlation(PPM) and Spearman Rank Correlation. The results of this research indicate that,1) the creative thinking skills of class V students are still in the low category at 56.2) the students' narrative essay writing skills are still in the sufficient category asevidenced by the average result of 60 being in the sufficient category. 3) there is nocorrelation between creative thinking skills and narrative essay writing skills forclass V students, amounting to 0.172. So, from the results of the research that hasbeen conducted, there is no positive and significant correlation between the abilityto think creatively and the narrative essay writing skills of class V students.Keywords: creative thinking skills, narrative essay writing skills.